A COMPARATIVE STUDY OF EFFICACY AND TOLERABILITY OF ANTIANGINAL DRUGS OF DIFFERENT GROUPS — NITROVASODILATATOR (ISOSORBIDE-5-MONONITRATE SUSTAINED RELEASE) AND BETA-BLOCKER WITH VASODILATING ACTION (NEBIVOLOL) — IN PATIENTS WITH STABLE ANGINA - S. Yu. Martsevich; N. P. Kutishenko; V. A. Egorov; A. V. Zagrebel'nyy; A. A. Serazhim; Yu. V. Lukina; N. A. Dmitrieva (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To compare the efficacy and safety of the slow-release isosorbide-5-mononitrate and of the nebivolol in patients with stable angina. Material and Methods. Patients (n=19) with ischemic heart disease (stable angina) were enrolled into randomized, double-blind, placebo-controlled, crossover study. They alternatively received nebivolol 5 mg QD or slow-release isosorbide-5-mononitrate 50 mg QD. The drug efficacy was assessed by changes in symptoms, angina attack number , sublingual nitroglycerin need, and treadmill test duration. Results. Patients treated with isosorbide-5-mononitrate shown significant increase in heart rate (HR) at rest in all time check-points in comparison with patients receiving placebo. HR significantly decreased 2 hours after nebivolol intake both single one and after 30 days of treatment (p<0.001). Duration of treadmill exercise significantly increased (vs placebo) 2 hours after a single intake of both isosorbide-5-mononitrate (454.3±37.1 vs 310.6±13.3 s; p <0.001) and nebivolol (428.6±33.3 vs 310.6±13.3 s; p<0.01). In one month of treatment isosorbide- 5-mononitrate and nebivolol reduced a number of angina episodes vs placebo (5.6±2.1 and 4.3±1.4, respectively , vs 8.6±2.4 episodes per month; p<0.05), the need for nitroglycerin (5.5±2.6 and 3.1±1.2, respectively , vs 6.7±2.2 sublingual tablets/month; p>0.05). No significant differences of these indicators were found between studied drugs. Conclusion. Nebivolol 5 mg daily is not inferior to slow-release isosorbide-5-mononitrate 50 mg daily in antianginal efficacy , significantly reduces HR, and much less causes headache and other side effects.